Relationships between plasma amino acid concentrations and blood pressure in South Africans of African descent - Naidoo, Cameron; Cromarty, Alan D.; Snyman, Tracy; Sliwa, Karen; Libhaber, Elena; Essop, Mohammed R.; Candy, Geoffrey P. (SA Heart Journal, 2017)
Oral supplementation with the amino acid arginine, the precursor of the vasodilator nitric oxide (NO), is associated with a reduction in blood pressure (BP). However, it is uncertain whether a decreased plasma arginine concentration predicts increases in BP. We assessed the relationship between fasting plasma arginine or other amino acid concentrations and 24 hour ambulatory BP in 75 nevertreated participants recruited from the Johannesburg area, 55 of whom were male. Plasma amino acid concentrations were measured with high performance liquid chromatography-mass-spectrometry. Plasma arginine concentrations were not inversely correlated with ambulatory BP. However, plasma arginine concentrations were increased in 36 participants with a mean daytime systolic BP >140 mm Hg (61 ± 17 μmol/L) as compared to the remaining participants (54 ± 15 μmol/L, p‹0.05). Moreover, plasma arginine concentrations were positively correlated with 24-hour diastolic BP (r=0.26, p‹0.05). In males with a BMI‹30kg/m2, plasma arginine concentrations were positively correlated with both night diastolic (r=0.46, p‹0.005) and systolic (r=0.42, p‹0.005) BP. In a multivariate model with adjustments for age gender, body mass index, and other amino acid concentrations, plasma arginine concentrations were independently and positively associated with night diastolic BP (p‹0.05). In conclusion plasma arginine concentrations are positively associated with ambulatory BP in a group of participants of African descent in South Africa. These data do not support the notion that deficiencies of arginine, the amino acid substrate for NO, are related to increases in BP in groups of African ancestry living in South Africa. However, as with other ethnic groups, the positive relationship between plasma arginine concentrations and BP suggests a reduced capacity to utilise the amino acid substrate for NO synthesis.